Variability analysis of dry spells for improving agribusiness management in Lesotho - Hlalele, Bernard M. (OASIS, 2020)
In sub-Saharan Africa, rain-fed agriculture remains one of the major sources of food, employment for low-skilled and rural community members and income for both commercial and subsistence farmers. Understanding problems posed by dry spells variability on agribusinesses is one of the critical challenges of our time. This study characterised dry spells in Lesotho for the improvement of agribusinesses using standardised precipitation (SPI) and standardised precipitation evapotranspiration (SPEI) drought indices. This study was found imperative mainly because Basotho's livelihood is dependent on rain-fed agriculture and this study further aimed to provide an early warning system that could be used for policymaking against adverse effects of drought events in the area. A 30-year-long rainfall and average monthly temperature data were collected from 10 administrative districts of Lesotho and used to compute SPI and SPEI values. Three dry spell parameters - frequency, duration and intensity - were derived from SPI and SPEI time series. The main findings of this study were that all candidate stations experienced similar dry spell conditions in both duration and frequency and all the selected stations throughout the country experienced extreme drought intensity levels from both SPI and SPEI. Two of the 10 districts showed a statistically significant decrease in Mann Kendal's trend from both SPI and SPEI time series. This implied that farmers must be encouraged to grow drought-resistant cultivars in order to sustain and support agribusiness in Lesotho. Rangeland policies and legislations must be enforced for livestock production, especially in the periods when extreme dry spell events are expected. The government and all other relevant stakeholders are, therefore, encouraged to devise means to support farmers with irrigation systems to maintain agricultural production, revenue and employees' employment status.
Keywords: Dry spell; Drought; Disaster; Agribusiness; Lesotho; Spectral analysis